Single Institution Experience with Tru-Cut Renal Mass Biopsy for Diagnosing Wilms Tumor - Cost, Nicholas G; Granberg, Candace F; Schlomer, Bruce J; Wickiser, Jonathan E; Gargollo, Patricio C; Baker, Linda A; Rakheja, Dinesh (Urology Journal, 2013)
PURPOSE: To evaluate the efficacy of needle biopsy for diagnosing Wilms tumor (WT) before chemotherapy. MATERIALS AND METHODS: We reviewed our institutional experience with Tru-Cut biopsy of pediatric renal masses in patients who subsequently underwent nephrectomy. We compared biopsy pathology with nephrectomy specimens to determine if biopsy accurately predicted final pathology. RESULTS: Seven children underwent Tru-Cut renal mass biopsy followed by surgical resection. In 4 patients, the final biopsy pathology was definitively read as WT and in 3 subjects, the pathology was read as WT versus hyperplastic nephrogenic rest. In all 7 patients, the nephrectomy pathology confirmed a diagnosis of WT. There were no complications after biopsy, and no patients have had local or regional recurrence. CONCLUSION: In our experience, pre-therapy Tru-Cut biopsy safely provides an adequate specimen for pathologic review in diagnosing WT.